Public governance and global politics after COVID-19 (2020)
The COVID-19 crisis is a major shock to the existing complex of global rules sometimes described as the “liberal international order.” This order heavily emphasized global openness in trade and information flows, and it favored the presumptive liberalization of non-democratic societies that would naturally emerge from it. Yet the liberal order fell short of its promise to create enduring liberal governments in countries such as Egypt during the Arab Spring and China. The long-standing liberal democracies at the core of the order have become less enamored of openness than they used to be. The limitations of the current version of the liberal international order had begun to emerge even before the COVID-19 pandemic. In part, these fractures resulted from a mismatch between the international order’s objectives and its assumptions about democratic publics. While policy makers assumed that international rule systems were in the interests of democratic publics,1 in practice those systems were insulated from them and sometimes even forcibly repressed them.2 This constrained democracy at the national level, as controversial decisions were kicked upstairs to less directly responsive global institutions. The rules governing areas such as trade and intellectual property were strong, while those for issues such as global health were weak, even if, as Janice Stein observes, the strong rules on trade required buy-in from powers such as the United States to function properly.